Declining male births in Germany before and after reunification - Grech, Victor (The Turkish Journal of Pediatrics, 2013)
Male births occur 3% in excess of female births in mammals in a ratio (M/F) of 0.515. Many factors have been shown to influence this, including socioeconomic deprivation. This paper reviews live birth data for Germany over the period 1946-2009, and identifies secular trends in M/F pre- and post-reunification. The null hypothesis is that there were no differences between East and West Germany, geographically or temporally, before and after reunification. Annual data on male and female live births were obtained from the Human Mortality Database and analyzed with contingency tables. These data were available separately for East and West Germany (1950-1989). There was a significant decline in M/F in both German Republics overall and before reunification (p